Determinant of users’ satisfaction towards Perpustakaan Raja Tun Uda / Mastura Muhamad and Mohamed Fadzli Mohd Fauzi - Muhamad, Mastura; Mohd Fauzi, Mohamed Fadzli (Faculty of Information Management, 2013)
This study examined users' satisfaction towards Raja Tun Uda Library as a yardstick for determining their level of satisfaction towards library services offered by this library. When Perpustakaan Raja Tun Uda moved to a new library, the library management decided to introduce new transformation in its service to its users, including improvement towards the contemporary interior designs. The rebranding of the library services and the building itself has attracted a crowd of over 4,000 visitors in weekdays and 5,000 to 6,000 during weekends. This overwhelming response from users' triggered the management to look at users' overall satisfaction towards the library new services and also the core services provided by the library. This research is limited to the main library of Perpustakaan Raja Tun Uda but does not cover the other 95 branches of the Selangor Public Library. In this study, the instrument selected was the self administered questionnaire. The study used Raosoft Sample size calculator to determine the appropriate number of respondents. The total number of 311 respondents who participated include library members and non-library members who visited this library. The findings of this study revealed that the users' are satisfied with the overall services of Perpustakaan Raja Tun Uda, Shah Alam.